Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran Discovery Learning - Grisselda Vania Putri; Erna Noor Savitri; Hernis Setiana (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This research is a classroom action research that aims to improve students' critical thinking skills through the application of the Discovery Learning learning model. This research was conducted in class VIII G of SMP Negeri 20 Semarang in the even semester of the 2022/2023 academic year with 32 students. This research was conducted in three cycles. Data obtained based on the results of observations and tests. Data collection was carried out using descriptive comparative statistical analysis. The research subjects were class VIII G with a total of 32 students. The results of the first cycle of research showed that the students' critical thinking skills were in the very high category 6.25%, the high category was 12.50%, the medium category was 62.50%, and the low category was 18.75%. In cycle II the increase was shown from the students' critical thinking skills in the very high category 40.62%, the high category 37.50%, the medium category 15.62%, the low category 6.25%, and the very low category did not exist. In cycle III the increase was shown from the students' critical thinking skills in the very high category 65.62%, the high category 28.12%, and the medium category 6.25%. The results showed that the Discovery learning model was proven to be able to improve students' critical thinking skills, where the indicator of the success of this study was an increase in the average value of mastery of critical thinking skills during learning in each cycle. Thus it can be concluded that the use of the Discovery Learning learning model can improve critical thinking skills which have an impact on improving student learning outcomes.